Helicobacter pylori Infection in Children with Recurrent Abdominal Pain - Badriul Hegar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2001)
Recurrent abdominal pain (RAP) is a very common presenting complaint in pediatric population. There is still a debate regarding the role of Helicobacter pylori (H. pylori) infection as an etiology of RAP. Typically, the inflammatory process in the gastric mucosa of infected individuals is chronic gastritis. Serologic and histologic examination are widely used for the diagnosis. This study was aimed to determine the role of H. pylori infection in Indonesian children with RAP. The presence of serum IgG antibody to H. pylori and upper gastrointestinal endoscopy were performed on the 101 children with RAP. Mucosal biopsies were obtained for histologic analysis. The prevalence of H. pylori infection indicated by serology was 32.7% and by histology was 27.7%. Histologic evidence of gastritis was present in 94.1% children and 45% of them had chronic atrophic and active gastritis. Seventy percent children with H. pylori  positive were found abnormal through endoscopy and all of the infected children were revealed abnormal through histological examination. Forty eight percent of seropositive children were found H. pylori positive and 80% of seronegative’s children were found to be H. pylori  negative through histologic examination. Conclusion: H. pylori infection can be a cause of RAP in children. Work up for H. pylori infection should be performed when symptoms are suggestive of organic disease. Larger prospective studies are needed to be performed for a longer time of period to clarify this issue.    Keywords: H. pylori infection, IgG antibody to H. pylori, upper GI endoscopy, RAP, recurrent abdominal pain